Analysis of Investment Outlays on Environmental Protection and Water Management in Rural Areas in Poland - Joanna SZYMANSKA; Anna OLSZANSKA; Anna S. KOWALSKA; Klaudia PASKUDZKA (Communications of International Proceedings, 2025)
The primary aim of the study was to analyze investment outlays on environmental protection and water management in rural areas in Poland between 2005 and 2020. The study sought to understand the directions and sources of financing these investments and their implications for sustainable rural development. While there has been broader research on environmental protection, there is limited focus on the structure, dynamics, and financing of environmental and water management investments specifically in rural areas of Poland. This study fills that gap by providing a detailed, long-term analysis of financial flows and investment priorities in these sectors. The study employed desk research methods, utilizing descriptive, analytical, mathematical, and statistical approaches. It involved an in-depth analysis of investment outlays by both investment direction and financing source over selected years. The analysis revealed that the largest share of investment was directed toward collective sanitation infrastructure. Other significant areas included sewage treatment plants and water treatment systems, while landfills received the least investment. Local government budgets were the primary source of funding, followed by EU Structural Funds and other environmental funds. The study observed an overall upward trend in investment levels but highlighted the need for accelerated action in landfill modernization. The results offer a valuable foundation for more localized future research.
Keywords: investment expenditure; environmental protection; water management; rural areas; Poland